Exploring the Operative Strategy for Secondary Mitral Regurgitation: A Systematic Review - Nappi, Francesco (Biomed Res Int, 2021)
BACKGROUND: Mitral valve disease surgery is an evolving field with multiple possible interventions. There is an increasing body of evidence regarding the optimal strategy in secondary mitral regurgitation where the pathology lies within the ventricle. We conducted a systematic review to identify the benefits and limitations of each surgical option. METHODS: A systematic review of the literature was performed to identify pertinent randomized controlled trials (RCTs), propensity-matched observational series, and meta-analyses which were considered initially and followed by unmatched observational series using the MEDLINE, Ovid EMBASE, and Cochrane Library. RESULTS: We identified 6 different strategies for treating secondary mitral valve regurgitation: mitral valve replacement, restrictive mitral annuloplasty, surgical revascularization (with and without mitral annuloplasty), subvalvular procedures (papillary muscle approximation, papillary muscle relocation, ring and string procedure), and procedures directly targeting the mitral valve (edge-to-edge repair and anterior leaflet enlargement) alongside transcatheter heart valve therapy. We also highlighted the role of left ventricular assist devices in the management of this condition. The benefits and limitations of each intervention are highlighted. CONCLUSION: There is currently no unanimous and shared strategy for the optimal treatment of patients with secondary IMR. The management of patients with secondary mitral regurgitation must be entrusted to a multidisciplinary Heart Team to ensure ideal intervention and patient matching for the best outcomes.